Ambrosiaster: Contre les Païens et Sur le Destin. Edited by Marie-Pierre Bussières - Winterbottom, Michael (The journal of theological studies, 2008)
We possess a good deal that was written by ‘Ambrosiaster’, in particular a commentary on the Pauline epistles and a large number of Questions on the Old and New Testaments. Yet surprisingly little is known of him. He was not even given a name to distinguish him from Ambrose or Augustine, to whom his works had been falsely attributed, till the end of the seventeenth century; the attempt to identify him preoccupied Germain Morin for thirty years, without success. It seems clear that he was writing around the time of Pope Damasus (d. 384), and at Rome. But that is all. He was not, in any case, a man of original intellect; he writes at times repetitively and without cogency, and his Latin leaves much to be desired.